2015
DOI: 10.1038/hdy.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Does population size affect genetic diversity? A test with sympatric lizard species

Abstract: Genetic diversity is a fundamental requirement for evolution and adaptation. Nonetheless, the forces that maintain patterns of genetic variation in wild populations are not completely understood. Neutral theory posits that genetic diversity will increase with a larger effective population size and the decreasing effects of drift. However, the lack of compelling evidence for a relationship between genetic diversity and population size in comparative studies has generated some skepticism over the degree that neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 36 publications
5
84
4
2
Order By: Relevance
“…Under neutral theory, a given population's genetic diversity is dependent on both the effective population size and the mutation rate (Kimura, ). Larger effective populations typically show greater genetic diversity than smaller populations (Hague & Routman, ), though some comparative studies have questioned this relationship (Bazin, Glémin, & Galtier, ). The conclusions of the present study are therefore based on the assumption of similar effective population sizes at these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Under neutral theory, a given population's genetic diversity is dependent on both the effective population size and the mutation rate (Kimura, ). Larger effective populations typically show greater genetic diversity than smaller populations (Hague & Routman, ), though some comparative studies have questioned this relationship (Bazin, Glémin, & Galtier, ). The conclusions of the present study are therefore based on the assumption of similar effective population sizes at these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found positive relationships between heterozygosity and proxies for species abundance, including population size estimated from calculations of density and acreage (Patton & Yang, ), extrapolations calculated from active social groups (Stangel, Lennartz, & Smith, ), categorical estimates (“large,” “small”) of population size (Godt, Johnson, & Hamrick, ; Hague & Routman, ) and museum occurrence records (Singhal, Huang, et al, ). Studies that more directly compare intraspecific genetic diversity and abundance have reported positive associations, but these studies have generally focused on single species or paired species comparisons (Devillard, Santin‐Janin, Say, & Pontier, ; Lozier, ; Ortego, Aparicio, Cordero, & Calabuig, ; Sun, ), or on many species sampled at a broad geographical scale (Bazin, Glémin, & Galtier, ; Leimu, Mutikainen, Koricheva, & Fischer, ; McCusker & Bentzen, ; Pinsky & Palumbi, ).…”
Section: Introductionmentioning
confidence: 99%
“…"small") of population size (Godt, Johnson, & Hamrick, 1996;Hague & Routman, 2016) and museum occurrence records (Singhal, Huang, et al, 2017). Studies that more directly compare intraspecific genetic diversity and abundance have reported positive associations, but these studies have generally focused on single species or paired species comparisons (Devillard, Santin-Janin, Say, & Pontier, 2011;Lozier, 2014;Ortego, Aparicio, Cordero, & Calabuig, 2008;Sun, 1996), or on many species sampled at a broad geographical scale (Bazin, Glémin, & Galtier, 2006;Leimu, Mutikainen, Koricheva, & Fischer, 2006;McCusker & Bentzen, 2010;Pinsky & Palumbi, 2014).…”
mentioning
confidence: 99%
“…He was then averaged over 195 the two populations and further considered as a proxy for effective population sizes. Both theoretical 196 and empirical works indeed indicate that genetic diversity should increase with the increase in 197 effective population sizes(Hague & Routman, 2016;Kimura, 1983; see also Appendix S4). We here 198 focused on mean heterozygosity because, unlike metrics such as allelic richness, heterozygosity values 199 are bounded between 0 and 1, which facilitates comparison between case studies.…”
mentioning
confidence: 94%